The Application of Humanistic Learning in Facing the Challenges of Modern Education: A Study of Literature - Esby Nuzulia; A. Ratnawati; Fatimah Azis; Kaharuddin (Aksiologi : Jurnal Pendidikan dan Ilmu Sosial, 2025)
This study aims to examine the application of humanistic learning to address the challenges of modern education through a literature review approach. Humanistic learning emphasizes the holistic development of students' potential, including cognitive, affective, and psychomotor aspects, and places students at the center of the learning process. Amidst globalization, the development of digital technology, the demand for modern-day skills, and the increasing complexity of socio-cultural issues, a humanistic approach is considered relevant for maintaining the human dimension in education. This study analyzes various scientific literature discussing the concept of humanism, humanistic learning models, and their implementation in various modern educational contexts. The results indicate that humanistic learning can enhance students' intrinsic motivation, creativity, emotional engagement, and learning independence. Furthermore, this approach can counterbalance the tendency toward dehumanization in technology-based education. However, the study also identified various challenges, such as limited teacher competency, school cultural resistance, and the suboptimal integration of curricula that support learner-centered learning. The study concludes that the application of humanistic learning remains relevant and needs to be strengthened through teacher training, the provision of supportive learning environments, and educational policies that emphasize human values.